The General features of Architecture and art of pilgrim churches in the Holy Land in the Middle Ages (comparative study) - Rasha Abdel Moneim (Journal of Architecture, Art & Humanistic Science, 2021)
The pilgrimages of the Christian world were centered in cathedrals and churches along the pilgrim routes of the Compostela Cathedral, St. Peter's Basilica in Rome and the Holy Land .The Holy Land is the oldest and most important of them. The Research Problem: Were the Holy Land churches considered pilgrimage churches in the medieval Christian world? Do religious beliefs have an impact on the architectural designs of worship places? What is the role of Bible in building these churches? Research Objectives: Presenting the Holy City (Jerusalem), its names, and the first Mother Church in history. Emphasizing the role of Emperor Constantine and his mother St. Helena in establishing the Christian religion and Jerusalem churchesReviewing the pilgrimage churches in the middle Ages in Jerusalem, Nazareth, Bethlehem, Galilee Al-Tabgha, Tabar, Beit Hasda, Anya, Mount of Olives, and the Via DolorosaComparing the architecture and arts of these churches with each other to describe and analyze their artworks with regards to their general characteristicsAscertaining the role of the Bible in recording the most important events and religious figures, their impact on the construction of Jerusalem churches Define the rituals of the pilgrimages in the eastern Christian world Designating similarities and differences between Jerusalem churches and middle Ages churches Methodology: a historical, descriptive and comparative analysis Importance: a sufficient, comprehensive study of a complete triple series of pilgrimage churches and cathedrals in the Christian world Methodology: a historical, descriptive and comparative analysis Importance: a sufficient, comprehensive study of a complete triple series of pilgrimage churches and cathedrals in the Christian world